2011
DOI: 10.1590/s1807-59322011000700011
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine for the prevention of shivering during spinal anesthesia

Abstract: PURPOSE:The aim of this study was to evaluate the effect of dexmedetomidine on shivering during spinal anesthesia.METHODS:Sixty patients (American Society of Anesthesiologists physical status I or II, aged 18-50 years), scheduled for elective minor surgical operations under spinal anesthesia with hyperbaric bupivacaine, were enrolled. They were administered saline (group C, n = 30) or dexmedetomidine (group D, n = 30). Motor block was assessed using a Modified Bromage Scale. The presence of shivering was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
89
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 31 publications
11
89
1
1
Order By: Relevance
“…Moreover, shivering, nausea and vomiting were also less in the dexmedetomidine group compared with the morphine group, consistent with other studies. [25][26][27][28] The low incidence of shivering might reflect a decreased shivering threshold and a lower core temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, shivering, nausea and vomiting were also less in the dexmedetomidine group compared with the morphine group, consistent with other studies. [25][26][27][28] The low incidence of shivering might reflect a decreased shivering threshold and a lower core temperature.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Other control agents included fentanyl, [33][34][35][36] remifentanyl, 37,38 meperidine, 15 midazolam, [39][40][41] propofol, 43,44 ketamine, 45,46 tramadol, 24,47 clonidine, 42 propacetamol, 48 and buprenorphine 49 ( 8 were reported in the 39 included trials, and all studies reported every endpoint mentioned in the Methods section (reporting bias). 8 however, some bias 8 may exist in of the two trials, 27,32 as the length of surgery was not clear.…”
Section: Study Characteristicmentioning
confidence: 99%
“…Intravenous Dexmedetomidine in dose range of 0.5 to 1 mcg/kg has been used successfully used either for prevention [14,[67][68][69] or treatment [70][71][72] of shivering after general or regional anaesthesia. Intravenous dexmedetomidine 0.5 mcg/kg as loading dose was found 100% effective in treatment of post anaesthesia shivering following general anaesthesia in children [72].…”
Section: Use Of Dexmedetomidine As Anti-shiveringmentioning
confidence: 99%
“…Apart from prolonging analgesia, it has been used for prevention and treatment of shivering [14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%